Induction of apoptosis in MDA-MB-231 breast cancer cells by a PARP1-targeting PROTAC small molecule. Issue 3 (12th December 2018) - Zhao, Qiuye; Lan, Tianlong; Su, Shang; Rao, Yu
Abstract : We report for the first time a PARP1-targeting PROTAC small molecule to selectively induce the cleavage of PARP1. Abstract : Poly (ADP-ribose) polymerase-1 (PARP1) is a major member of the PARP superfamily that is involved in DNA damage signalling and other important cellular processes. Here we report the development of a small molecule targeting PARP1 based on the PROTAC strategy. In the MDA-MB-231 cell line, the representative compound3 can induce significant PARP1 cleavage and programmed cell death.